La fuerza de los caminos sonoros: caminata y música en Qoyllurit’i - Mendoza, Zoila (Pontificia Universidad Católica del Perú. Fondo Editorial, 2010)
Here I explore the intrinsic relationship that for the people of the district of Pomacanchi (Cusco) exists between walking to the sanctuary of the Lord of Qoyllurit’i and the music that accompanies them. My attention focuses on the relationship with the chakiri wayri melody and to a lesser extent with that called alawaru. In this intrinsic relationship between music and the walk, on the one hand, the primacy of the unity of the visual and the auditory in the Andean cognitive processes reveals itself. On the other hand, in exploring this relationship in the context of the walk a third sensorial dimension key to such cognitive processes appears clearly. It is the sense of kinesthesia or sensation of movement. In other words. The unity of the visual, the auditory and the kinesthetic is what makes the participation in the fiesta of the Lord of Qoyllurit’i a unique and unforgettable experience. The obvious primacy of the unity of these three senses in the experience of pilgrimage of the people of Pomacanchi to the sanctuary of the Lord of Qoyllurit’i is not unique or exclusive of this festive context or of Pomacanchi. Simply, this experience allows us to analyze more closely a phenomenon that I believe to be spread in the Andes.

En este trabajo exploro la relación intrínseca que existe para los pobladores del distrito de Pomacanchi, Cusco, entre el caminar al santuario del Señor de Qoyllurit’i y la música que los acompaña. Mi atención se centra en la relación con la melodía chakiri wayri y, en menor medida, con la del alawaru. En esta relación intrínseca entre música y camino se revela, por un lado, la primacía que para los pobladores andinos tiene la unidad de lo visual y lo auditivo en los procesos cognitivos. Por otro, al explorar esta relación en el contexto de la caminata, una tercera dimensión sensorial clave en dichos procesos cognitivos también aparece claramente. Se trata del sentido de la cinestesia o sensación del movimiento. En otras palabras, la unidad de lo visual, lo sonoro y el movimiento es lo que hace de la participación en la fiesta en honor al Señor de Qoyllurit’i una experiencia única e imborrable. La obvia primacía de la unidad de los tres sentidos en la experiencia de peregrinación de los pomacanchinos al Señor de Qoyllurit’i no es única o exclusiva de este contexto festivo o de este pueblo. Simplemente esta experiencia nos permite analizar más de cerca un fenómeno que creo extendido en los Andes.
The strength of the sounding paths: the Walk and Music in Qoyllurit’i
Keywords: Peregrinación; Cusco; Música; Caminata; Experiencia sensorial; Procesos cognitivos; Chakiri wayri; Alawaru; https://purl.org/pe-repo/ocde/ford#5.04.03